The implementation of genome sequencing in rare genetic diseases diagnosis: a pilot study from the Hong Kong genome projectResearch in context - Wai Kei Jacky Lam; Chak Sing Lau; Ho Ming Luk; Lisa Wing Chi Au; Gary C.P. Chan; Will Yap Hang Chan; Shirley Sze Wing Cheng; Timothy Hua Tse Cheng; Li Li Cheung; Yiu Fai Cheung; Josephine Shuk Ching Chong; Annie Tsz Wai Chu; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Genome sequencing (GS) has revolutionised the diagnostic odyssey of patients with rare genetic diseases (RDs) and accelerated large-scale genome projects globally. However, the impact of GS on patients with RDs is yet to be investigated among genome projects in Asia. The Hong Kong Genome Project (HKGP) was implemented to benefit patients and families with RDs in Hong Kong, and to increase the inclusiveness of Chinese genomic data. This study evaluated the impact of short read GS (srGS), complemented by long read GS (lrGS) in a subset, on individuals recruited in the pilot phase of the HKGP. Methods: GS was performed on a prospective cohort of patients with suspected genetic disease recruited by territory-wide referrals to the HKGP. All participants received srGS, while lrGS was applied to a subset to resolve technically challenging regions unclear from srGS and provide phasing information for potential compound heterozygous variants. A phenotypic-driven diagnostic workflow was implemented to filter and prioritise rare and likely disease-causing variants. The primary outcome was diagnostic yield. The impact on the diagnostic odyssey and clinical management was also assessed. Findings: A total of 1264 individuals from 520 families with a broad spectrum of RDs were recruited, with 94% of probands being Chinese. srGS was performed for all individuals and lrGS was performed in 21 individuals. The use of srGS achieved a molecular diagnosis in 24% (125/520) of probands, and an additional 4% (21/520) with the assistance from lrGS. Approximately one-third of the identified diagnostic variants being novel. Diagnostic yield was found to be significantly higher among adult probands compared to paediatric probands (32% vs 24%; p = 0.025). The diagnostic yield was significantly higher in probands without prior genetic testing (37%; n = 185) compared to those previously tested, including exome and genome sequencing (23%; n = 335) (p = 0.001). GS ended diagnostic odysseys with an average length of 15 years (0.5–59), and potentially impacted clinical management in 77% (113/146) of diagnosed probands. Interpretation: This population-based genome project shed light on the consideration of integrating srGS and lrGS in clinical workflows for RDs. The identification of unique and prevalent variants from Southeast Asia increased the inclusiveness of Chinese genomic data, contributing to greater representation and genomic diversity. Funding: The HKGP is a publicly funded genome sequencing initiative commissioned by the Health Bureau of the HKSAR Government.